Neurological Soft Signs and Psychopathology in Chronic Schizophrenia: A Cross-Sectional Study in Three Age Groups - Herold, Christina J.; Lässer, Marc M.; Seidl, Ulrich Wilhelm; Hirjak, Dusan; Thomann, Philipp A.; Schröder, Johannes (Frontiers in Psychiatry, 2018)
As established in a wealth of studies subtle motor and sensory neurological abnormalities or neurological soft signs (NSS) are frequently found in patients with schizophrenia at any stage of their illness. However, the potential impact of chronicity and age on NSS was scarcely investigated. Therefore, we assessed NSS in 90 patients with subchronic (n=22) or chronic (n=68) schizophrenia and in 60 healthy controls who were assigned to three age groups (18-29 years, 30-49 years, +50 years). NSS were measured on the Heidelberg Scale, psychopathological symptoms including apathy were rated on established instruments. As demonstrated by ANOVA, NSS scores in patients were significantly (p<0.05) increased relative to healthy controls. Significant age effects arose in all NSS subscores, with older subjects scoring well above the younger ones. These age effects were more pronounced in patients than controls, indicating that NSS in chronic schizophrenia exceed age-associated changes. Moreover, the NSS scores in patients were significantly associated with duration of illness, thought disturbance, positive symptoms and apathy. These results were confirmed after age/duration of illness and years of education were partialed out and via regression analyses. Our findings conform to the hypothesis that NSS are associated with chronicity of the disorder as indicated by the correlations of NSS with both, duration of illness and apathy. The correlations between NSS and positive symptoms/thought disturbance correspond to the fluctuation of positive symptoms during the course of the disorder. The significantly more pronounced age effects on NSS in patients may either point to ongoing cerebral changes or to a greater susceptibility of patients towards physiological age effects, which may be mediated among other factors by a lower cognitive reserve.